2022
DOI: 10.1108/jkm-06-2021-0421
|View full text |Cite
|
Sign up to set email alerts
|

The role of cloud computing in knowledge management for small and medium enterprises: a systematic literature review

Abstract: Purpose Knowledge management (KM) is widely adopted by organisations to improve their performance and make informed decisions. Prior research has confirmed that Information Systems (IS) play a critical role in effective KM. The purpose of this study is to examine the existing literature on the role of cloud-based KM systems (C-KMS) in small- and medium-sized enterprise (SMEs) by understanding its impact on the five KM processes: knowledge acquisition, creation, storage, sharing and usage. Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Nonetheless, these works only focus on how platform artifacts are created by digital platforms. They do not directly address the core idea of this study, which is whether or not the KI processes in digital platforms play an important role in crisis management (Saratchandra and Shrestha, 2022). The results of this study enrich our research perspectives through quantitative analysis but differ from those of other studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nonetheless, these works only focus on how platform artifacts are created by digital platforms. They do not directly address the core idea of this study, which is whether or not the KI processes in digital platforms play an important role in crisis management (Saratchandra and Shrestha, 2022). The results of this study enrich our research perspectives through quantitative analysis but differ from those of other studies.…”
Section: Discussionmentioning
confidence: 95%
“…A relevant insight from this perspective is that cultural, linguistic, regulatory and spatial constraints, result in less interpretability of globalization impediments compared to localized impediments (Collings et al , 2019). Hence, due to knowledge gap in how cross-border businesses can best weather COVID-19, coupled with the generally ad hoc methods of addressing crises, multinational SMEs as global businesses may be more vulnerable to a crisis such as COVID-19 (Saratchandra and Shrestha, 2022). Support-seeking multinational SMEs will mainly focus on their knowledge gaps and, therefore, will likely seek to actively integrate knowledge that gives them a holistic understanding what is currently ambiguous – i.e.…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The follow-up review, through the analysis of 180 articles, structures insights from the current literature categorised by themes that address different aspects of KM and thus takes into account not only the variety but also the complexity of KM in SMEs. The presented paper is not limited to very limited areas of KM in SMEs research, as it has been the case with several reviews that have been published recently, such as Cerchione et al (2016), Costa et al (2016), Anand et al (2021) or Saratchandra and Shrestha (2022); thus, the present review provides more holistic and recent insights into the diversity of the research field over a longer period (2012–2022).…”
Section: Discussionmentioning
confidence: 99%
“…Six papers were assigned to this category (see Table 16). Saratchandra and Shrestha (2022) been shown in the study by Kim and Ahn (2020), while Crupi et al (2020) showed how European digital innovation hubs could take the role of knowledge brokers to support digital transformation in SMEs. Finally, Scuotto et al (2021) showed the relevance of developing dynamic capabilities for improving marketing KM.…”
Section: Table 11 Articles On Knowledge Measurement and Performancementioning
confidence: 93%